2013
DOI: 10.2478/v10200-012-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Third instar larva morphology of Hydrotaea cyrtoneurina (ZETTERSTEDT, 1845) (Diptera: Muscidae) – a species of forensic interest

Abstract: ABSTRACT. The muscid Hydrotaea cyrtoneurina (ZETTERSTEDT, 1845) is a Palaearctic species whose adults are known for their forensic importance. The third instar larva morphology of H. cyrtoneurina, hitherto unknown, is described herein with the application of light and scanning electron microscopy. The characters of larval morphology enabling this species to be distinguished from other forensically important third instar larvae of Muscidae are discussed as well. Some details of the cephaloskeleton are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…Except for the most recent studies (e.g. Grzywacz, 2013;Grzywacz et al, 2013Velasquez et al, 2013;Grzywacz & Pape, 2014), none of the previous reports observed sensilla surrounding the spiracular field in third instars of Muscidae. However, the studies by Grzywacz et al (2013) and Velasquez et al (2013) are incomplete because these authors did not recognize the sensilla resembling sensilla ampullacea (i.e.…”
Section: Comparative Morphologymentioning
confidence: 78%
See 4 more Smart Citations
“…Except for the most recent studies (e.g. Grzywacz, 2013;Grzywacz et al, 2013Velasquez et al, 2013;Grzywacz & Pape, 2014), none of the previous reports observed sensilla surrounding the spiracular field in third instars of Muscidae. However, the studies by Grzywacz et al (2013) and Velasquez et al (2013) are incomplete because these authors did not recognize the sensilla resembling sensilla ampullacea (i.e.…”
Section: Comparative Morphologymentioning
confidence: 78%
“…Except for the most recent studies (e.g. Grzywacz, ; Grzywacz et al ., , ; Velasquez et al ., ; Grzywacz & Pape, ), none of the previous reports observed sensilla surrounding the spiracular field in third instars of Muscidae. However, the studies by Grzywacz et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations